1984
DOI: 10.1051/rnd:19840508
|View full text |Cite
|
Sign up to set email alerts
|

Sperm transport in the cow : peri-ovulatory redistribution of viable cells within the oviduct

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0
4

Year Published

1984
1984
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(114 citation statements)
references
References 15 publications
4
106
0
4
Order By: Relevance
“…Moreover, a 70% incidence of fertilization followed intraperitoneal insemination of small volumes of boar semen shortly before ovulation (Hunter, 1978), so a continuous pre-ovulatory progression of spermatozoa up and out of the control oviduct in the present work might have been expected to lead to some fertilizations in the transected oviduct. Taking these observations together, and also the results of comparable surgical studies in sheep (Hunter & Nichol, 1983) and cows (Hunter & Wilmut, 1984), the evidence strongly favours the concept of pre-ovulatory sequestering of viable spermatozoa in the caudal region of the oviduct isthmus. A similar situation occurs in the oviducts of rabbits (Harper, 1973a, b ;Overstreet, Cooper & Katz, 1978 ; and the golden hamster (Yanagimachi & Chang, 1963;Battalia & Yanagimachi, 1979), although Harper (1973a) suggests that it is the "products of ovulation", the eggs, their investments and/or the follicular fluid, entering the oviducts that leads to movement of spermatozoa towards the site of fertilization.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, a 70% incidence of fertilization followed intraperitoneal insemination of small volumes of boar semen shortly before ovulation (Hunter, 1978), so a continuous pre-ovulatory progression of spermatozoa up and out of the control oviduct in the present work might have been expected to lead to some fertilizations in the transected oviduct. Taking these observations together, and also the results of comparable surgical studies in sheep (Hunter & Nichol, 1983) and cows (Hunter & Wilmut, 1984), the evidence strongly favours the concept of pre-ovulatory sequestering of viable spermatozoa in the caudal region of the oviduct isthmus. A similar situation occurs in the oviducts of rabbits (Harper, 1973a, b ;Overstreet, Cooper & Katz, 1978 ; and the golden hamster (Yanagimachi & Chang, 1963;Battalia & Yanagimachi, 1979), although Harper (1973a) suggests that it is the "products of ovulation", the eggs, their investments and/or the follicular fluid, entering the oviducts that leads to movement of spermatozoa towards the site of fertilization.…”
Section: Discussionmentioning
confidence: 86%
“…Du Mesnil du Buisson and Dauzier [5] had suspected that either the utero-tubal junction or the isthmus might act as a sperm reservoir, and by surgical and histological studies the latter was shown to be true in pigs [6], sheep [7] and cows [8,9]. We termed the caudal portion of the isthmus the functional sperm reservoir [10], for it was from this region of the tract that spermatozoa involved in the events of fertilisation were activated and released close to the time of ovulation.…”
Section: Functional Sperm Reservoirmentioning
confidence: 99%
“…The isthmus part is described as functioning as a sperm reservoirsperm adhere to the epithelium and at the time of ovulation they are released (Hunter & Wilmut 1984) to ensure the perfect timing of fertilisation. In this way, the oviduct provides the microenvironment for sperm capacitation, fertilisation, and early embryonic development (Buhi 2002).…”
Section: Introductionmentioning
confidence: 99%